Steven-Johnson Syndrome associated with anti-tuberculosis drugs: a case reports - I Gusti Ayu Risma Pramita; Tjokorda Dalem Pemayun (DiscoverSys Inc., 2020)
Introduction: Steven-Johnson syndrome (SJS) is an acute reaction to the skin and mucous membranes that is characterised by damage and flaking of the skin, accompanied by pain and can cause death. Treatment with anti-TB drugs sometimes results in side effects including SJS Â as one of the skin rash reaction and liver dysfunction. Steven-Johnson syndrome incidence and mortality due to anti-TB is quite rate and here we present a case with SJS and some other drugs side effect symptoms who passed away on the ninth day of treatment.Â Case description: A 53-year-old woman admitted to our emergency department with dyspnea, fatigue, erosion on oral mucosa, and erythema appears in the whole body accompanied by itch since two weeks ago, she also has yellowish sclera. She is in ongoing therapy of anti-tuberculosis drugs. History of hepatitis B, on admission there was marked elevation of leukocyte and liver function test (AST and ALT). Systemic corticosteroid was given as characterised therapy with topical steroid and antibiotics regimen for maculopapular rash.Conclusion: SJS is an emergency requiring high attention and intensive care evaluation with administration of intravenous systemic steroids as primary immunosuppressive therapy.